Altered Expression of Circulating miR-223-3p in Patients with Idiopathic Recurrent Pregnancy Loss: A Case and Control Study - Parisa Ostad Hasanzadeh; Saeid Ghorbian; Jafar Mohseni; Sedigheh Abdollahi Fard; Changiz Amadizadeh (International Journal of Fertility and Sterility)
Background: Circulating microRNAs (miRNAs or miRs) are key regulators of a wide array of biological processesthat aberrantly express under physiological as well as pathological conditions. This study aims to determine whetheraltered expression of circulating miR-223-3p in plasma is associated with an increased risk of idiopathic recurrentpregnancy loss (iRPL), and if it could be a novel non-invasive biomarker for diagnosis of iRPL.Materials and Methods: In this case and control study, Plasma samples were obtained from 60 women with a historyof ≥ 2 consecutive miscarriages and 60 women with at least one full-term pregnancy and no history of miscarriage.The samples were used to assess the expression of circulating miR-223-3p by quantitative real-time polymerase chainreaction (qPCR) and determine the correlation between patient clinico-demographic parameters and miR-223-3p expressionlevels. We used receiver operating characteristic (ROC) curve analysis to evaluate the diagnostic accuracy ofmiR-223-3p for the diagnosis of iRPL.Results: There was significant up-regulation in miR-223-3p expression in patients with iRPL compared with healthycontrols (P=0.002). No significant correlation was found between the expression level of miR-223-3p and the numberof miscarriages in iRPL patients (P=0.344). ROC curve analysis revealed that the area under the curve (AUC) valuefor miR-223-3p was 0.658 [95% confidence interval (95% CI): 0.5590.757, P=0.002).Conclusion: These results suggest that a higher expression level of circulating miR-223-3p may be closely relatedwith the increased risk of iRPL and possibly serve as a promising non-invasive diagnostic biomarker for iRPL.